2015
DOI: 10.1037/aca0000019
|View full text |Cite
|
Sign up to set email alerts
|

A completion mindset: Bridging the gap between creative thinking and creativity.

Abstract: Anecdotal and scientific evidence has documented the relationship between students trained in creative thinking and novel idea generation. Creative thinking can be taught; however, cognitive traits must be developed for creative thinking to be manifested in output, which requires ego-strength and a completion mindset. For creativity to be realized, students need to develop the drive and commitment to bring a creative idea to fruition. Neuro-education can be effective in highlighting brain optimization as integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Defined as the process by which people think and act to produce novel works ( Guilford, 1950 ), creativity was said to comprise four steps: preparation, incubation, illumination, and verification ( Wallas, 1926 ). After decades of extensive research, a deeper understanding developed of the competencies, characteristics, and cognitive processes associated with creativity ( Plucker et al, 2004 ; Cadle, 2015 ), and researchers took a more nuanced and interdisciplinary approach to understanding creativity ( Goswami, 1996 ). For example, a recent grounded-theory study proposed that the creative process for journalists goes through four stages: cognition, cultivation, capture, and reflection ( Rubenstein et al, 2017 ).…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%
“…Defined as the process by which people think and act to produce novel works ( Guilford, 1950 ), creativity was said to comprise four steps: preparation, incubation, illumination, and verification ( Wallas, 1926 ). After decades of extensive research, a deeper understanding developed of the competencies, characteristics, and cognitive processes associated with creativity ( Plucker et al, 2004 ; Cadle, 2015 ), and researchers took a more nuanced and interdisciplinary approach to understanding creativity ( Goswami, 1996 ). For example, a recent grounded-theory study proposed that the creative process for journalists goes through four stages: cognition, cultivation, capture, and reflection ( Rubenstein et al, 2017 ).…”
Section: Theoretical Basis and Hypothesesmentioning
confidence: 99%
“…The study implied that the stronger the value of creative thinking, the better the efforts among the families to overcome poverty because of a positive relationship. The concept of self-creativity is still difficult to translate or test since humans live in various situations, cultures, religions or ideologies (Cadle, 2015). Creative thinking involves four aspects: the availability of a mind-based process, the manufacture of a product, human involvement and a place or premise for creativity to occur (Kozbelt, Beghetto, & Runco, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Creativity is said to incorporate four stages: arrangement, incubation, clarification, and confirmation ( Xu et al, 2021 ). After tens of years of comprehensive exploration, a more profound comprehension has been built regarding the capabilities, attributes, and intellectual cycles related to creativity, and scholars have adopted a more subtle and interdisciplinary method for comprehending creativity ( Cadle, 2015 ). For instance, new grounded-theory research suggested that the creative cycle for journalists involves four steps: intellect, improvement, capture, and contemplation ( Rubenstein et al, 2013 ).…”
Section: Review Of the Literaturementioning
confidence: 99%